Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1097/ede.0b013e31816a9dcb
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Pulmonary Function in Asthmatic Children

Abstract: Prenatal and early-life exposures to CO, PM10, and NO2 have a negative effect on pulmonary function in subgroups of asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 24 publications
1
67
1
2
Order By: Relevance
“…The recent INMA cohort study found that in utero exposures, more specifically during the second trimester of pregnancy, may be more relevant for long-term adverse consequences for lung function than exposures later in life (Morales et al, 2015). A USA cohort study of 232 asthmatic children indicated that the association between allergic sensitization at 6-11 years of age and exposure to air pollution during pregnancy was stronger in the first and second trimesters (Mortimer et al, 2008). Another USA cohort study also found deficits in offspring lung function at preschool age in relation to maternal short-term exposure to traffic-related air pollutants (PM 2.5 ) in the second trimester of pregnancy (Jedrychowski et al, 2010).…”
Section: Eczema Asthmamentioning
confidence: 98%
“…The recent INMA cohort study found that in utero exposures, more specifically during the second trimester of pregnancy, may be more relevant for long-term adverse consequences for lung function than exposures later in life (Morales et al, 2015). A USA cohort study of 232 asthmatic children indicated that the association between allergic sensitization at 6-11 years of age and exposure to air pollution during pregnancy was stronger in the first and second trimesters (Mortimer et al, 2008). Another USA cohort study also found deficits in offspring lung function at preschool age in relation to maternal short-term exposure to traffic-related air pollutants (PM 2.5 ) in the second trimester of pregnancy (Jedrychowski et al, 2010).…”
Section: Eczema Asthmamentioning
confidence: 98%
“…25 Namely, there have been associational studies that document correlations between in utero exposure to each of maternal smoking and pollutants such as carbon monoxide and asthma later in life (e.g., Stick et al 1996;Gilliland, Li, and Peters, 2001;Mortimer et al, 2008). We note that apart from only reporting correlations, the exact biological pathways in utero connecting these to asthma remain unclear.…”
Section: Study IImentioning
confidence: 88%
“…The lung function impairment is also associated with occupational asthma and exposure to air pollution. 38,39 Some children show only mild, transient and sporadic episodes of airway obstruction that does not lead to chronic asthma. Depending upon the severity of asthmatic episodes, it can be further classified as in Table 2.…”
Section: -18mentioning
confidence: 99%